2013
DOI: 10.1177/1077801213499244
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Date Rape Perceptions

Abstract: The effects of participant gender and victim resistance on date rape perceptions have been inconsistent. Participant gender role attitudes may contribute to these inconsistencies. We found women with traditional gender role attitudes were least likely to agree that the perpetrator was guilty of rape. Participants were less convinced of the perpetrator's guilt when the victim resisted verbally than when she resisted verbally and physically, and participants with traditional gender role attitudes were less convi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
(75 reference statements)
0
24
1
Order By: Relevance
“…However, some research has demonstrated a lack of gender differences, and researchers have suggested that the relationship between gender and attributions is mediated by attitudes about gender (Abrams, Viki, Masser, & Bohner, 2003; I. Anderson & Lyons, 2005; Angelone, Mitchell, & Grossi, 2015; Angelone, Mitchell, & Lucente, 2012; K. A.…”
Section: Observer Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some research has demonstrated a lack of gender differences, and researchers have suggested that the relationship between gender and attributions is mediated by attitudes about gender (Abrams, Viki, Masser, & Bohner, 2003; I. Anderson & Lyons, 2005; Angelone, Mitchell, & Grossi, 2015; Angelone, Mitchell, & Lucente, 2012; K. A.…”
Section: Observer Characteristicsmentioning
confidence: 99%
“…In addition, lower levels of victim blame are associated with verbal or physical resistance relative to when no overt resistance is displayed (Cohn et al, 2009; Ryckman, Kaczor, & Thornton, 1992). Observers are also less likely to agree that the victim should report the incident or find the perpetrator guilty when she verbally resists as opposed to combined verbal and physical resistance (K. A.…”
Section: Situational Characteristicsmentioning
confidence: 99%
“…Individuals who have been assaulted by someone they know are the least likely to seek support from the police. This is concerning given that 90% of rape perpetrators are known to the victim, either casually or romantically (Black & McCloskey, 2013). Although there are many reasons why victims are reluctant to report acquaintance rape to the police, it has been suggested that a major reporting barrier is the woman's fear that police will question the veracity and credibility of their claims, or even blame them for the assault.…”
Section: Rapementioning
confidence: 99%
“…When stereotypes are repeatedly advanced by sources that people consider reliable, especially authority figures such as members of the clergy, politicians and educators, they are frequently taken as truth and adopted (Black et al, 2013;Moskowitz et al, 2012;Peterson et al, 1990;Punt, 2009;Tan et al,1996). It seems quite reasonable to us that one might include scholars and academics in this list of trusted people.…”
Section: Stereotypingmentioning
confidence: 99%